Proper Assessment Impact Towards Corporate Sustainability Case Study : PT ANTAM - UPBE Pongkor - Sukada, Nawandha Ilaga; Rudito, Bambang (Journal of Business and Management, 2013)
Indonesia as the country with abundant natural resources inevitable attract both domestic and international companies to exploit these natural resources for business interest, especially those who specialize with mining industry. Mining industry is in fact creating an impact towards the state of environment and community where the company does its business activities. To minimize the impact to the environment and community, respected company has to create Corporate Social Responsibilities. In attempt to create a benchmark for the Corporate Social Responsibilities program, the Indonesian government trough Kementrian Lingkungan Hidup (KLH) established PROPER program to assess the CSR program that the companies implemented. The purpose of this final project is to research whether the PROPER program is assisting companies to create a better quality of CSR programs trough its regulations and assessments. This final project is also researching the impact on PROPER program assessment to the corporate sustainability, in this context towards PT. Antam sustainability. The result of the program will also be analyzed to discover whether it is already accomplish its target or not. The Author will analyze the relation between PROPER assessment and the corporate sustainability to determine the strength and weakness of PROPER program. To achieve the objectives above the Author interviewed some of the biggest responsibilities holder in CSR field of PT Antam and experts in CSR fields, including those who helped KLH create the PROPER program. To get the results, the Author is using these methodology, Research Design, Problem Identification, Data Gathering, Data Analysis, and Conclusion. The conclusion of this research is PROPER program does direct companies to create strategic CSR program, shown by its regulations, terms, and conditions. But the post-assessment creates no tangible impacts to corporate sustainability. For the recommendation first is to make universal standard for its assessment, second is to create a reward and punish system after assessment, and third provide personnel proportional to the amount of companies assessed. Keywords: corporate social responsibility, PROPER, case study.---------------------------------DISCLAMER: This paper is created by undergraduate students of School of Business and Management ITB in partial fulfillment of the requirement of the degree Bachelor of Management. Journal of Business and Management is not responsible for the content, opinions, or any other materials expressed here.